Determinat Factors The Effect Used Personal Protective Equipment Covid-19 For Health Workers in The Hospital - Alfina Baharuddin; Hasriwiani Habo Abbas; Fetrawaty Mansyur (Indian Journal of Forensic Medicine & Toxicology, 2021)
Purpose: to analyze the determinants of the use of Covid-19 PPE (Personal Protective Equipment) on healthworkers at Salewangang Hospital, Maros Regency.Methods: The type of research used is the analytical survey method of research conducted withoutintervention to the research subject. Data collection regarding free and dependent variables was carriedout online using Google Form and the results of Google Form data collection were processed using SPSS20, where a sample of 199 respondents was taken from health workers at Salewangang Maros RegionalHospital in 2020. The analysis was used to explain the influence of the variables - independent variables tothe dependent variable partially using Logistic Regression Analysis.Results: Based on the results shows that knowledge has a 12-fold effect on behavior The use of Covid 19PPE and the attitude of health workers has a significant effect on the behavior of using the OR value of 16.6,which means that attitudes have a 16.6-fold effect on the behavior of using Covid 19 PPEConclusion: Based on this study, it is concluded that the availability of PPE, knowledge and attitudes ofhealth workers have a significant effect on the behavior of using PPE Covid-19 with a significant value of0.000?0.05.